A Comparative Study of Software Firewall on Windows and Linux Platform (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Nowadays, the communication through World Wide Web (WWW) is growing rapidly. All the gadgets, computer and handheld devices are connected via wire or wireless media and communicated to each others. Thus, network security is the essential requirement of an organization or individuals. Organizations are protecting their communication from unauthorized access by introducing network firewalls. A Firewall is an application program which runs on any platform such as windows, Linux, Solaris, Macintosh etc and protected the networks or systems via implementing policies and rules. In this paper, the performance of firewall is measured and compared on Windows and Linux platform individual. To evaluate the performance, a private network has been setup in which three machines are connected via a switch; one Windows machine running windows firewall, one Linux machine running Linux firewall (IPTable) and one more machine that acting as a client. On both the platforms, the performance is measured in two situations: first when network is traffic free and second network with traffic. When network is traffic free then both the platforms reflect the common normal processing behavior in context of time and packet received per second; and when packets are pumped at a very high speed in the network then the processing time and packet received per second increases exponentially in both the platforms.